KELAYAKAN FLIPCHARTMATERI KEANEKARAGAMAN HAYATI DARI BUAH JAMBU MAREKAN, KANDIS, DAN PISANG KAROK - Selviana, Uray; Daningsih, Entin; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the feasibility of flipchart media on biodiversity material in class X SMA from the results of morphology and nutritional content jambu marekan fruit fiber (Bellucia pentamera Naudin), kandis (Artocarpus dadah Miq), and pisang karok (Musa campestris Becc. Var. Sarawakensis Hakkinen) encountered at the Sibohe Pajintan Singkawang Timur forest in Singkawang City in West Kalimantan. This research form is descriptive using purposive sampling technique with two stages, namely instrument validation and media validation. The validation instrument used contains 6 aspects and 16 criteria. Data were analyzed using the Lawshe method with the Content Validity Ratio (CVR) and Content Validity Index (CVI) formulas and validated by five validators. Two validators are lecturers of biological education, while three other validators are high school biology teachers who use the 2013 curriculum in the Singkawang. The results of the validation showed that the instrument was feasible to be used and repaired, while the results of the flipchart media validation obtained CVR and CVI values up to 0.99 which corresponded to Lawshe's minimum CVI value for five validators so that the flipchart media was declared valid and feasible to used as learning media on class X biodiversity material High school.Keywords:Biodiversity, Flipchart, Jambu Marekan, Kandis, Pisang Karok